(3QSGdI aj Yde GdEcSjQs
(3ChdgG (B:s
(3bO jPcQhf HYV CLhGA GdMLQ heY Pdc jVjahf Edjg eG jaSOg hjSQbhf GdJOHjQ Edi BNQ GdYed Ydi LhgQ aGSO s
(3BNQgG (B:s
(3GdSGHY YTQ cjajI QLhYg Edi GdMGdI GdeQVjI MJi jUHZ GdUHZ GdeWdhH hGdMeO dhGgH GdYbd heajV GdQMeI hMSHfG Gddg hfYe Gdhcjd hgh MSHfG hcai HGddg MSjHkG hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde JSdjekG cKjQkG OGFekG CHOkG Edi jhe GdOjf Bejfs
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQg ahGFOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs